Biodegradable external wrapping promotes favorable adaptation in an ovine vein graft model. (1st October 2022) - Ramachandra, Abhay B.; Wang, Hanjay; Wnorowski, Alexa; Schwarz, Erica L.; Pickering, Joshua; Heiler, Joseph C.; Lucian, Haley J.; Hironaka, Camille E.; Tran, Nicholas A.; Liu, Yu; Khan, Muhammad Owais; Obafemi, Oluwatomisin; et al.
Abstract: Vein grafts, the most commonly used conduits in multi-vessel coronary artery bypass grafting surgery, have high intermediate- and long-term failure rates. The abrupt and marked increase in hemodynamic loads on the vein graft is a known contributor to failure. Recent computational modeling suggests that veins can more successfully adapt to an increase in mechanical load if the rate of loading is gradual. Applying an external wrap or support at the time of surgery is one way to reduce the transmural load, and this approach has improved performance relative to an unsupported vein graft in several animal studies. Yet, a clinical trial in humans has shown benefits and drawbacks, and mechanisms by which an external wrap affects vein graft adaptation remain unknown. This study aims to elucidate such mechanisms using a multimodal experimental and computational data collection pipeline. We quantify morphometry using magnetic resonance imaging, mechanics using biaxial testing, hemodynamics using computational fluid dynamics, structure using histology, and transcriptional changes using bulk RNA-sequencing in an ovine carotid-jugular interposition vein graft model, without and with an external biodegradable wrap that allows loads to increase gradually. We show that a biodegradable external wrap promotes luminal uniformity, physiological wall shear stress, and a consistent vein graft phenotype, namely, it prevents over-distension, over-thickening, intimal hyperplasia, and inflammation, and it preserves mechanotransduction. These mechanobiological insights into vein graft adaptation in the presence of an external support can inform computational growth and remodeling models of external support and facilitate design and manufacturing of next-generation external wrapping devices. Statement of significance: External mechanical support is emerging as a promising technology to prevent vein graft failure following coronary bypass graft surgery. While variants of this technology are currently under investigation in clinical trials, the fundamental mechanisms of adaptation remain poorly understood. We employ an ovine carotid-jugular interposition vein graft model, with and without an external biodegradable wrap to provide mechanical support, and probe vein graft adaptation using a multimodal experimental and computational data collection pipeline. We quantify morphometry using magnetic resonance imaging, mechanics using biaxial testing, fluid flow using computational fluid dynamics, vascular composition and structure using histology, and transcriptional changes using bulk RNA sequencing. We show that the wrap mitigates vein graft failure by promoting multiple adaptive mechanisms (across biological scales). Graphical abstract: Image, graphical abstract